Florida Landowner Incentive Program - William M. Giuliano (EDIS, 2006)
WEC-212, a 2-page illustrated fact sheet, describes the Florida Fish and Wildlife Conservation Commission (FWC)'s program to provide science-based recommendations and financial assistance to landowners for adopting practices that conserve and enhance Florida's habitat resources on private lands. Published by the UF Department of Wildlife Ecology and Conservation, May 2006.